2020
DOI: 10.1016/j.eucr.2019.101074
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic malignant fibrous histiocytoma in bladder diverticulum

Abstract: The Malignant Fibrous Histiocytoma is a very rare cancer and rather exceptional when located in bladder diverticulum. it occurs in men in their sixties, manifests itself through haematuria and/or irritative micturition. There is not a causal association. An immunohistochemical analysis is necessary to establish a differential diagnosis. It is aggressive, with a high rate of local recurrence and remote progression, thereby requiring early treatment that consists of radical cystectomy with pelvic lymph node diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, only a few cases of primary MFH arising in the urinary bladder have been reported. Previous studies have reported a total of 33 cases up until 2020 ( 5 6 7 ). We summarized the clinical and radiological features of bladder MFHs described in previous case reports, mainly in cases in which the radiological findings were well described ( Supplementary Table 1 in the online-only Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only a few cases of primary MFH arising in the urinary bladder have been reported. Previous studies have reported a total of 33 cases up until 2020 ( 5 6 7 ). We summarized the clinical and radiological features of bladder MFHs described in previous case reports, mainly in cases in which the radiological findings were well described ( Supplementary Table 1 in the online-only Data Supplement).…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike urothelial carcinoma, which is often diagnosed when it is small owing to symptoms of hematuria, MFH is most often a large mass at the time of diagnosis. MFH tends to present as a large mass without central necrosis ( 9 ) and is characterized as a “non-papillary tumor” that tends to invade the deep muscular layer of the bladder wall, with 83% of cases known to be at T3 or higher stages ( 5 ). Generally, cancers derived from mesenchymal cells tend to be more diffuse in nature, whereas urothelial carcinomas tend to be more localized ( 9 ).…”
Section: Discussionmentioning
confidence: 99%